Bioequivalence Study of Two Letrozole Tablet Formulations - Filipe, Augusto; Almeida, Susana; Spínola, Ana Cristina Franco; Trabelsi, Fethi; Ortuño, Jordi (Arzneimittelforschung, 2008)
The study was conducted in order to compare the bioavailability of two tablet formulations containing letrozole 2.5 mg (CAS 112809-51-5). Twenty healthy subjects were enrolled in a single-centre, bioequivalence, randomised, single-dose, open-label, two-way crossover study, performed under fasting conditions with a minimum washout period of 21 days. Plasma samples were collected up to 240 h post-dosing. Letrozole levels were determined by reverse liquid chromatography and detected by tandem mass spectrometry detection, LC/MS/MS method. Pharmacokinetic parameters used for bioequivalence assessment, area under the concentration-time curve from time zero to time of last non-zero concentration (AUC0–t) and from time zero to infinitive (AUC0–inf) and maximum observed concentration (Cmax), were determined from the letrozole concentration data using non-compartmental analysis.The 90% confidence intervals obtained by analysis of variance were 90% geometric confidence intervals of the ratio (A/B) of least-squares means from the analysis of variance (ANOVA) of the In-transformed AUC0–t, and Cmax was within 80% to 125%. Bioequivalence between formulations was concluded both in terms of rate and extent of absorption.
Keywords: Anticancer agents; CAS 112809-51-5; Letrozole, bioequivalence